The role of action representations in thematic object relations - Tsagkaridis, Konstantinos; Watson, Christine E.; Jax, Steven A.; Buxbaum, Laurel J. (Frontiers in Human Neuroscience, 2014)
Recent studies assessing the role of associative/event-based (thematic) and categorical (taxonomic) relations in the organization of object representations suggest that thematic relationships may influence the perceived similarity of manipulable artifacts. At the same time, evidence suggests that action knowledge is an important component of manipulable artifact representations. However, the role that action plays in processing thematic relationships between objects is unclear. In this study, we assessed healthy and left hemisphere stroke participants to explore three questions: 1. Do participants favor thematic relations involving action (Th+A, e.g., wine bottle – corkscrew), thematic relationships without action (Th-A, e.g., wine bottle – cheese), or taxonomic relationships (Tax, e.g., wine bottle – water bottle) when choosing between them in an association judgment task? 2. Do the underlying constructs of event, action, and categorical relatedness implicitly determine the choices that participants make? 3. Does degraded action knowledge and/or damage to temporo-parietal cortex (a region of the brain associated with action representations) reduce the influence of action on the choice task? Experiment 1 showed that explicit ratings of event, action, and categorical relatedness differentially predicted healthy participants’ choices, with action relatedness determining choices between Th+A and Th-A associations above and beyond event and categorical ratings. Experiment 2 focused more specifically on these Th+A vs. Th-A choices and demonstrated that participants with left temporo-parietal lesions, a brain region known to be involved in sensorimotor processing, were less likely than controls, and tended to be less likely than patients with lesions sparing that region, to implicitly use action knowledge in determining their choices. We conclude that action knowledge plays a critical role in processing of thematic relations for manipulable artifacts.